Perspectivas de representatividade da mulher nas relações entre trabalho e educação na agrovila de Placas, Pitinga, Breu Branco – Pará - SOUSA, Aliene da Silva (Instituto Federal de Educação Ciência e Tecnologia do Pará, 2022)
The families in the region of Agrovila of Placas, Pitinga, Breu Branco- Pará were characterized in the central figure of the father, and this, was usually the administrator of the family's savings and social influences. The sons helped their father in the land chores, the mother, along with her daughters, were responsible for the household activities. But in the course of time, the women of the Agrovila began to play a more prominent role in the community's economic activities. Faced with this problem, the present work aims to analyze how women conceive perspectives of representative relations between work and education in Agrovila of Placas, Pitinga, Breu Branco – Pará and elaborate a pedagogical notebook with scripts of didactic sequences, which proposes reading and writing activities that promote the valorization of the community's identity and culture, as well as the natural patrimony, through the rescue, preservation and registration of this patrimony, thus making it possible to recognize the relevance of the work developed by women of the community for the rural development of the community. The research received a qualitative approach, consisting of bibliographic research and field research. Initially, we sought to reflect on the importance of women in the social construction of work in the field and the relation of rural education to the valorization of peasant women's identity and the work done by them, besides making a historical, social, economic, and political panorama of the Agrovila of Placas. Through the field research, it was possible to collect historical data about the community, as well as to perceive how the community understands the work of the women in the community, the influence of women's education and work on local rural development. The analysis of the collected data happened by means of graphing and discourse analysis of the interviews and the focus group, this allowed us to see how the women in the community manage to articulate tasks from the private space and public spaces, with the family as the center of reference. The study also made it possible to document the history and knowledge of the community that resulted in the preservation of events and memories, which generated recognition of the relevance of the work done by women of the community to promote local rural development.